Diary drawings : mental illness and me - Baker, Bobby, 1950-; Warner, Marina, 1946-; Whittuck, Andrew; Whittuck, Dora (London : Profile, 2010)
In 1996 the artist Bobby Baker was diagnosed as having borderline personality disorder. Her subsequent struggle to overcome severe mental and later physical illness lasted for 11 years. The 158 drawings and watercolours in this book are an astonishing record of her slow and harrowing journey to eventual recovery.
Keywords: Baker, Bobby, -- 1950- -- Notebooks, sketchbooks, etc; Baker, Bobby, -- 1950- -- Mental health; Art and mental illness; Borderline personality disorder; Boek